2011
DOI: 10.1111/j.1365-2966.2011.18941.x
|View full text |Cite
|
Sign up to set email alerts
|

Galactic rotation curves in brane world models

Abstract: In the braneworld scenario the four dimensional effective Einstein equation has extra source terms, which arise from the embedding of the 3-brane in the bulk. These non-local effects, generated by the free gravitational field of the bulk, may provide an explanation for the dynamics of the neutral hydrogen clouds at large distances from the galactic center, which is usually explained by postulating the existence of the dark matter. In the present paper we consider the asymptotic behavior of the galactic rotatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 76 publications
2
38
0
1
Order By: Relevance
“…In this extra-dimensional context, the exterior r > R of a spherically symmetric self-gravitating system of radius R will be filled with a Weyl fluid of effective density U and anisotropy P µν . This fluid has interesting phenomenological consequences, and indeed may be used to explain some issues associated with the gravitational interaction beyond the Solar System scales [69]- [71].…”
Section: Field Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this extra-dimensional context, the exterior r > R of a spherically symmetric self-gravitating system of radius R will be filled with a Weyl fluid of effective density U and anisotropy P µν . This fluid has interesting phenomenological consequences, and indeed may be used to explain some issues associated with the gravitational interaction beyond the Solar System scales [69]- [71].…”
Section: Field Equationsmentioning
confidence: 99%
“…where the expressions in Eqs. (14) and (20) have been used in the field equations (5) and (6). Therefore, according to Eq.…”
Section: The Extension Of the Minimal Geometric Deformationmentioning
confidence: 99%
“…But, MOG must effectively become Milgromian on galaxy scales. In addition, it has been shown that flat rotation curves of galaxies can be accounted for without DM by brane-world models (Gergely et al 2011) as well as by f(R)-gravity models (Capozziello et al 2009) whereby lensing constraints are also being studied in these and other theories.…”
Section: No Dark Matter But Modified Gravitymentioning
confidence: 99%
“…Specifically, several classes of static, spherically-symmetric, solutions of the vacuum field equations on the brane have been obtained [64][65][66][67]. As a possible physical application of these solutions the behavior of the angular velocity, v tg , of test particles in stable circular orbits has been considered [66][67][68][69][70][71]. The general form of the solution, together with the specific values of the two, arbitrary, constants of integration, uniquely determines the rotational velocity of the particle.…”
Section: Introductionmentioning
confidence: 99%